Three Versus Six Months of Adjuvant Doublet Chemotherapy for Patients With Colorectal Cancer: A Multi-Country Cost-Effectiveness and Budget Impact Analysis - Hanna, Catherine R.; Robles-Zurita, José Antonio; Briggs, Andrew; Harkin, Andrea; Kelly, Caroline; McQueen, John; Allan, Karen; Pearson, Sarah; Hollander, Henrik; Glimelius, Bengt; Salazar, Ramon; Segelov, Eva; et al. (CIG MEDIA GROUP, LP, 2021)
Background: The Short Course Oncology Treatment (SCOT) trial demonstrated non-infer ior it y, less toxicit y, and cost- effectiveness from a UK perspective of 3 versus 6 months of oxaliplatin-based chemotherapy for patients with colorectal cancer. This study assessed the cost-effectiveness of shorter treatment and the budget impact of implementing trial findings from the perspectives of all countries recruited to SCOT: Australia, Denmark, New Zealand, Spain, Sweden, and the United Kingdom. Patients and Methods: Individual cost–utility analyses were performed from the perspective of each country. Resource, quality of life, and survival estimates from the SCOT trial ( N = 6065) were used. Probabilistic sensitivity analysis and subgroup analyses were undertaken. Using undiscounted costs from these cost–utility analyses, the impact on country-specific healthcare budgets of implementing the SCOT trial findings was calculated over a 5- year period. The currency used was US dollars (US$), and 2019 was the base year. One-way and scenario sensitivity analysis addressed uncertainty within the budget impact analysis. Results: Three months of treatment were cost saving and cost-effective compared to 6 months from the perspective of all countries. The incremental net monetary benefit per patient ranged from US$8972 (Spain) to US$13,884 (Denmark). The healthcare budget impact over 5 years for the base-case scenario ranged from US$3.6 million (New Zealand) to US$61.4 million (UK) and totaled over US$150 million across all countries. Conclusion: This study has widened the transferability of results from the SCOT trial, showing that shorter treatment is cost-effective from a multi-country perspective. The vast savings from implementation could fully justify the investment in conducting the SCOT trial.
Keywords: Cancer - Tratamiento; Clinical trial; Cost analysis; Drug therapy; International; Neoplasm